Elucidating the Reaction Mechanism of Atomic Layer Deposition of Al2O3with a Series of Al(CH3)xCl3- xand Al(CyH2 y+1)3Precursors - Oh, Il Kwon; Sandoval, Tania E.; Liu, Tzu Ling; Richey, Nathaniel E.; Nguyen, Chi Thang; Gu, Bonwook; Lee, Han Bo Ram; Tonner-Zech, Ralf; Bent, Stacey F. (Journal of the American Chemical Society, 2022)
The adsorption of metalorganic and metal halide precursors on the SiO2surface plays an essential role in thin-film deposition processes such as atomic layer deposition (ALD). In the case of aluminum oxide (Al2O3) films, the growth characteristics are influenced by the precursor structure, which controls both chemical reactivity and the geometrical constraints during deposition. In this work, a systematic study using a series of Al(CH3)xCl3-x(x = 0, 1, 2, and 3) and Al(CyH2y+1)3(y = 1, 2, and 3) precursors is carried out using a combination of experimental spectroscopic techniques together with density functional theory calculations and Monte Carlo simulations to analyze differences across precursor molecules. Results show that reactivity and steric hindrance mutually influence the ALD surface reaction. The increase in the number of chlorine ligands in the precursor shifts the deposition temperature higher, an effect attributed to more favorable binding of the intermediate species due to higher Lewis acidity, while differences between precursors in film growth per cycle are shown to originate from variations in adsorption activation barriers and size-dependent saturation coverage. Comparison between the theoretical and experimental results indicates that the Al(CyH2y+1)3precursors are favored to undergo two ligand exchange reactions upon adsorption at the surface, whereas only a single Cl-ligand exchange reaction is energetically favorable upon adsorption by the AlCl3precursor. By pursuing the first-principles design of ALD precursors combined with experimental analysis of thin-film growth, this work enables a robust understanding of the effect of precursor chemistry on ALD processes.
Keywords: Atomic-layer deposition; Film-deposition process; Geometrical constraints; Growth characteristic; Ligand exchange reactions; Metalorganics; Reaction mechanism; SiO2 surface; Systematic study; Thin-film depositions